x-(7)=13

Simple and best practice solution for x-(7)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(7)=13 equation:


Simplifying
x + -1(7) = 13

Multiply -1 * 7
x + -7 = 13

Reorder the terms:
-7 + x = 13

Solving
-7 + x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + x = 13 + 7

Combine like terms: -7 + 7 = 0
0 + x = 13 + 7
x = 13 + 7

Combine like terms: 13 + 7 = 20
x = 20

Simplifying
x = 20

See similar equations:

| 2x-7y-10=0 | | =2(a+3)+3(2a-1) | | 1.5(x-6)=-6 | | 2h=-12 | | x+0.03x=3000 | | 80-3x=5x+9 | | 6x-11=-2x+13 | | (24+8x+7y)-(4x+6y+56)=0 | | (7x-12)=(6y+8) | | 3t-2=10 | | 20r+15=365 | | (7x-12)-(-2x+3)= | | X^2+10x+C=-5+c | | 2500-40.5x=-3000 | | x-8=x-36 | | 15p+5=95 | | 9k+30=120 | | 10p+1=81 | | 2c+2=16 | | -2500-40.5x=-3000 | | 12+(-2)+7+4+(-6)= | | a=q^2+13q+23 | | 4y-2+y+29=6y+30-4y | | x-10=x-10 | | 7x+7x=48 | | (3x-15)-(-7x+4)= | | (2x+1)(2x)= | | 7(-3x+5)-1+-2-15x= | | 9(t^2)-6t+50=0 | | 5x+14=-14-9 | | -5y+8=-7 | | 8+2x-4=9x+7-4x |

Equations solver categories